Research on the effect of selective adsorption of CO2 by C@Fe3O4 for H2 purification - Longlong Lei; Hang Yuan; Hongguang Zhu; Jie Ma; Fanghui Pan; Fulu Lu (Carbon Capture Science & Technology)
In the context of global efforts to address climate change, capturing and storing CO2, as well as developing hydrogen energy, have emerged as widely recognized effective methods for reducing greenhouse gas emissions. In particular, the process of hydrogen production through the gasification and reforming of organic fuels necessitates the separation and purification of H2 from CO2. Although various technological pathways have been proposed in this research field, issues such as low separation efficiency, high energy consumption, and high costs are prevalent to varying degrees across these different methods. This study is based on reports of the strong interaction between ferric oxide (Fe3O4) and CO2, as well as the magnetic exclusion of hydrogen gas. This study hypothesize carbon-coated magnetite (C@Fe3O4) as a material with selective adsorption of CO2, enabling efficient separation of H2 and CO2. To test this hypothesis, this study synthesized C@Fe3O4 and conducted isothermal adsorption tests to determine the adsorption curves for H2 and CO2, along with calculations for adsorption selectivity. The results indicated that C@Fe3O4 exhibited good selectivity for CO2 over H2 under ambient conditions. Penetration experiments further confirmed that the separation ratio for H2 and CO2 reached as high as 13.6. Comparative experiments with porous carbon materials lacking the Fe3O4 core, along with characterization analyses of C@Fe3O4, validated the dual mechanism at play: the strong adsorption of CO2 by the Fe3O4 core and the magnetic exclusion of hydrogen. The carbon coating did not inhibit the strong adsorption of CO2 by Fe3O4 but also provided a barrier that prevented direct contact between H2 and Fe3O4, mitigating any potential reduction reactions that could lead to magnetic decay. Moreover, the petal-like carbon-coated structure increased the volumetric CO2 adsorption capacity of the material. Although the high density of the Fe3O4 crystalline core resulted in modest mass adsorption capacity, the unique layered carbon structure enhanced the specific surface area. This dual effect led to a volumetric CO2 adsorption capacity of 1.32 mmol/cm³, surpassing that of most existing porous carbon materials, and the CO2/H2 adsorption ratio also exceeded that of many carbon materials.